Best Conference Paper Award - Melanthiou, Yioula (My University, 2026)
Best Conference Paper Award at the 17th Annual Conference of the EuroMed Academy of Business, held in Pisa (Italy) the 11th-13th of September 2024
Keywords: Business and industry